The Impact of Comparative Literature on Education: A Multifaceted Perspective - Sharma, Harsh; Bhamra, Veerpal (International Journal of Advanced Research in Peace, Harmony and Education, 2024)
Comparative literature, as an academic discipline, holds a unique position in the realm of education. Its interdisciplinary nature allows for a multifaceted exploration of cultural, linguistic, and literary phenomena across different societies and historical periods. This article aims to delve into the various ways in which comparative literature influences education, from fostering critical thinking skills to promoting intercultural understanding and empathy. By examining the intersection of comparative literature and education, we can gain insights into how this discipline enriches learning experiences and contributes to the development of well-rounded individuals equipped to navigate an increasingly interconnected world.